Peran Museum Tebing Tinggi dalam Pelestarian Sejarah - Siti Adinda Fitria; Achiriah A; Kasron Muhsin Nasution (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the role of Tebing Tinggi City Museum as a cultural institution in efforts to preserve local history. The focus of the research is on how the museum functions as a center for collecting, maintaining, and presenting historical objects related to the heritage of Tebing Tinggi City, such as relics from the Serdang Sultanate and the colonial period, as well as its role in providing historical education to the community. This study employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews with museum staff, and documentation. The aim of the research is to analyze the museum’s contribution to preserving local history and to identify the challenges it faces, including limited budgets, a lack of professional human resources, and low public interest, particularly among younger generations. The results indicate that although the museum plays a strategic role in historical preservation and cultural education, these obstacles hinder its optimal performance. Strengthening collaboration among local government, museum management, and the community is necessary to enhance the museum’s function as a medium for the preservation and promotion of local history.